LAWS AND CUSTOMS OF WAR: QUALIFICATIONS - TOMA, MARIANA (Ehrlich's Journal, 2025)
The article is devoted to the coverage of theoretical and practical problems of the qualification of actions provided for in Art. 438 of the Criminal Code of Ukraine «Violation of laws and customs of war». Modern legislation, both national and international, stands on the positions of guarantees of recognition of a person, his rights and freedoms, as the highest social value, to ensure the activities of both the state authorities of specific individual countries and the entire international community as a whole. However, it is fundamental that basic human rights, recognized by international law, continue to exist and be protected both in peacetime and in wartime. The present makes adjustments to our lives every second and, unfortunately, they are not always positive. The terrible date in the calendar, February 24, 2022, the russian federation invaded the territory of sovereign Ukraine and began military operations to occupy it. Few people in the modern world would think that in the 21st century there is a place for such bloody crimes against humanity, which were known during the Second World War, but Ukraine faced them. Analyzing the features of the crime provided for in Article 438 of the Criminal Code of Ukraine, we came to the conclusion that the relevant provision is blanket and directs us to the norms of international humanitarian law on the law of war. The norms of international law themselves are not clearly defined, which requires the bodies of the pre-trial investigation and the court that issues a guilty verdict against convicted servicemen of the armed forces of the Russian Federation to clearly define which of the acts provided for in the disposition were violated in a specific case. Accordingly, the blanket disposition of the first part of Article 438 of the Criminal Code of Ukraine is called international law. In order to bring the culprits to justice, it is necessary to clearly indicate which specific Convention was violated by the suspect, with the accused noting its full official name, it is also necessary not only to indicate the names of the conventions, but also to indicate which specific articles of them constitute a violation of the laws and customs of war, as well as the absence of a reference as to the specific norms of international humanitarian law on the law of war, as well as to specific articles (parts thereof) of these norms, is a violation of the requirements for establishing the fact of the commission of the crime itself, which in the future may indicate a violation of the rights of the suspect, the accused to know what criminal offense was committed he is suspected and accused of a crime.